2017
DOI: 10.1371/journal.pone.0179406
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell neoplasia after kidney transplantation: French cohort series and review of the literature

Abstract: Although post-transplant lymphoproliferative disorder (PTLD) is the second most common type of cancer in kidney transplantation (KT), plasma cell neoplasia (PCN) occurs only rarely after KT, and little is known about its characteristics and evolution. We included twenty-two cases of post-transplant PCN occurring between 1991 and 2013. These included 12 symptomatic multiple myeloma, eight indolent myeloma and two plasmacytomas. The median age at diagnosis was 56.5 years and the median onset after transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(56 reference statements)
0
4
1
Order By: Relevance
“…Prior studies have reported a younger age of presentation of PT‐PCNs (median 56‐60 years) 41,42 compared to MM (median 68‐71 years), 53,54 although many included extraosseus plasmacytomas, which tend to occur in young patients 30 . The median age of diagnosis of PT‐PCMs in our series (68 years) was similar to MM, however, the incidence of bone disease (18%) was lower than that reported in MM (78%) 55 .…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…Prior studies have reported a younger age of presentation of PT‐PCNs (median 56‐60 years) 41,42 compared to MM (median 68‐71 years), 53,54 although many included extraosseus plasmacytomas, which tend to occur in young patients 30 . The median age of diagnosis of PT‐PCMs in our series (68 years) was similar to MM, however, the incidence of bone disease (18%) was lower than that reported in MM (78%) 55 .…”
Section: Discussioncontrasting
confidence: 37%
“…enabled ruling out all the differential diagnostic considerations in the current study.The pathogenetic mechanisms underlying PT-PCM development have not been clarified. Most studies did not evaluate EBV infection of the neoplastic plasma cells [41][42][43]. On analysis of the Transplant Cancer Match Study data, Engels et al found 4/8 (50%) PT-PCMs with available information to be EBV+, but results of imaging studies were not provided and other sites of disease were not mentioned 8.…”
mentioning
confidence: 99%
“…The development of cancers in general following transplantation is quite common [ 73 ]. Some studies have found a trend of lower risk of getting multiple myeloma after a kidney transplant, compared with the general population [ 74 , 75 ], whereas other studies found a higher incident of multiple myeloma following kidney transplantation [ 76 , 77 ]. Overall, it seems that giving tacrolimus to patients is safe, but that the patients might have an increased rate of infection.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Therefore, it is not surprising that immunodeficiency increases the risk of EBV-associated lymphoproliferative disorders. 11 EBV-positive plasma cell neoplasms are usually reported in post-transplant patients [12][13][14][15][16][17][18] and less commonly in HIV-positive patients, 3,[19][20][21][22][23] with the prevalence dramatically lower in immunocompetent individuals. 20 HIV predisposes infected individuals to many cancers, including several hematolymphoid malignancies.…”
Section: Introductionmentioning
confidence: 99%